Nexus between Family Socioeconomic Status and Alcohol Consumption Moderated by Religiosity among Secondary School Adolescents in Uganda - Bashaija, Athanansio; Rukundo, Aloysius (Journal of Education Research and Rural Community Development, 2020)
This paper focuses on the relationship between family socioeconomic status and alcohol consumption. It further covers the moderation effect of religiosity on the relationship between family socioeconomic status and alcohol consumption among secondary school adolescents in Bushenyi Ishaka Municipality in Uganda. The study employed a cross-sectional survey with quantitative method of data collection and analysis. The schools for the study were selected through a stratified proportionate sampling method. Schools were categorised into two strata; government and private secondary schools from which 6 of them were sampled and simple random sampling techniques were used to arrive at the final sample study of 404 participants from six schools. Data was collected using a self-administered questionnaire with standardised scales. The instrument comprised biodata, SES scale, religiosity, spiritual scale for Youth, and AUDIT Test for Alcohol use. Responses were obtained from a total of 404 participants who included females as the majority (54.7%). The mean age of the students was 15.91. Results show that there was a significant relationship between family socioeconomic status (SES) and alcohol consumption. Religiosity had significant positive moderation effect on the relationship between family socioeconomic status and alcohol consumption among secondary school adolescents. Religiosity is a strong resilience and deters adolescents from consuming alcohol regardless of their family socioeconomic status.
Keywords: Family socioeconomic status; Alcohol consumption; Religiosity; Secondary school adolescents